2023
DOI: 10.1002/cac2.12516
|View full text |Cite
|
Sign up to set email alerts
|

The Chinese Society of Clinical Oncology (CSCO): Clinical guidelines for the diagnosis and treatment of gastric cancer, 2023

Feng‐Hua Wang,
Xiao‐Tian Zhang,
Lei Tang
et al.

Abstract: The 2023 update of the Chinese Society of Clinical Oncology (CSCO) Clinical Guidelines for Gastric Cancer focuses on standardizing cancer diagnosis and treatment in China, reflecting the latest advancements in evidence‐based medicine, healthcare resource availability, and precision medicine. These updates address the differences in epidemiological characteristics, clinicopathological features, tumor biology, treatment patterns, and drug selections between Eastern and Western gastric cancer patients. Key revisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 363 publications
0
4
0
Order By: Relevance
“…The Cox model was used in some studies to show that the risk of death in stage III patients is 2.82 times that in stage II patients, and that in stage IV patients is 3.29 times that in stage II patients [ 21 ]. The presence of PTNM serves as a significant independent prognostic indicator for patients with gastric cancer patients [ 25 , 26 ] and can forecast patients’ prognosis and offer treatment recommendations. The prognosis of patients varied significantly across different disease stages.…”
Section: Discussionmentioning
confidence: 99%
“…The Cox model was used in some studies to show that the risk of death in stage III patients is 2.82 times that in stage II patients, and that in stage IV patients is 3.29 times that in stage II patients [ 21 ]. The presence of PTNM serves as a significant independent prognostic indicator for patients with gastric cancer patients [ 25 , 26 ] and can forecast patients’ prognosis and offer treatment recommendations. The prognosis of patients varied significantly across different disease stages.…”
Section: Discussionmentioning
confidence: 99%
“…The results of our study have suggested a tendency towards higher three-year disease-free survival rate with perioperative SOX for patients with resectable stage II/III gastric cancer compared to the adjuvant SOX. The results of the subgroup analysis provide compelling evidence supporting the recommendation in the Chinese guidelines for administering neoadjuvant chemotherapy in stage III patients [ 11 ]. The limitations of this study include potential deviations in stage or response evaluation, the absence of using Lauren’s classification and microsatellite instability status, and the uneven number of enrolled cases across different centers.…”
mentioning
confidence: 86%
“…These clinical trials successfully revealed that ICIs produce favourable GC therapeutic effects [ 57 ].…”
Section: Clinical Trials That Have Evaluated Immune Checkpoint Inhibi...mentioning
confidence: 99%